Landscape and overview of innovation activities in Philippine enterprises - Lim, Cristina Teresa Natividad (Animo Repository, 2021)
In this data age, there has been a rapid transformation of the way things are done as a result of innovation. Innovation has always been regarded as the key to business growth and development. For small and medium enterprises (SMEs) in the Philippines to remain competitive, they need to face these increasing demands which require more innovation. The purpose of this study is to present an overview of innovative behavior and perception among SMEs surveyed from the 2015 World Bank Enterprise Survey for the Philippines. Analysis of the innovation components such as product innovation, process innovation, marketing innovation, and organizational innovation and mapping of the main innovative activities were examined. Results showed that SMEs do exert effort to innovate products or processes, but their innovation rate is still much lower as compared to large enterprises. The results also showed that SMEs spend less on formal research and development (R&D) activities and have less purchase or license of any patented or non-patented inventions. Moreover, SMEs provide less formal training to any of its employees specifically for the development and/or introduction of new or significantly improved product services and processes. Innovation showed a negative covariance which means that innovation and R&D expenditures tend to move in inverse directions. This situation should allow the government to come up with national policy interventions that support and encourage innovation especially for the SMEs.